Investigación de la presencia de secuencias del virus de la necrosis hipodérmica y hematopoyética infecciosa (ihhnv) en el genoma del camarón penaeus vannamei - Sampedro Cruz, Carlos (2010)
Infectious Hypodermal and Hematopoietic Necrosis Virus (IHHNV) has been associated with deformities and growth retardation in Penaeus vannamei and other Penaeid shrimp. However, in many instances, this virus seems to co-exist with its host, with up to 100% of the members of a population being asymptomatic carriers. High prevalence of virus in the absence of disease may indicate the existence of a state of latency, and the integration of viral sequences in the host could provide a mechanism for IHHNV to establish such latency. The present study was conducted to determine the presence of IHHNV sequences integrated into the genome of P.vannamei, using Southern blot for the analysis of genomic DNA samples from adult shrimps. The results of this investigation showed no evidence of integration of IHHNV in the population of P.vannamei analyzed, despite observing a high prevalence of virus in the population. These results favor the hypothesis of infectious IHHNV as a source of the high viral prevalence observed in domesticated populations in Ecuador, although the possibility of integration of IHHNV in this and other populations cannot be ruled out on the bases of these studies alone.